OPINI TOKOH PARTAI POLITIK TERHADAP KEBERPIHAKAN TV ONE DAN METRO TV DALAM PILPLRES 2014 DI SULAWESI SELATAN - Belekebun, Susilawati; Unde, Andi Alimuddin; Cangara, Hafied (KAREBA : Jurnal Ilmu Komunikasi, 2015)
Abstract This research aimed(1) to investigate the opinions of the political party prominent figures toward the sidedness find out the master of political party opinion towards the sidedness of the TV One and Metro TV in 2014 presidential election; (2) To investigate the extent of the roles of the media in forming the opinions of the political party prominent figures toward the sidedness of TV One dan Metro TV; (3) to investigate the sidedness levels of TV One dan Metro TV as the national TVs in 2014 presidential election. The research was descriptive-qualitative in character. The research informants comprised 12 prominent figures of the political parties, 7 culturalists, political observers, and academicians. The samples were chosen using the purposive sampling technique. The data collection was through interviews and observation. Then the data analysis was done using the interaction model analysis developed by Miles and Huberman. The obtained data were processed through 3 qualtative data analysis channels, namely data reduction, data presentation, and conclusion drawing. The research results revealed that the opinions of the prominent figures of the political parties toward the sidedness of TV One and Metro TV in 2014 presidential election tended to take side with a certain couple, TV One tended to take side with the Pair of Prabowo-Hatta, while Metro TV tended to take side with the Pair of Jokkowi-JK. Also, the roles of the TV was very strong in forming the opinions of the prominent figures of the political parties in 2014 Presidentia Election as felt by all the informants â either by those joining the Merah Putrih Coalision (KMP) or those joining the Indonesia Hebat Coalision (KIH). The some opinions were also felt by the prominent figures of the political parties in South Sulawesi. This was possible because of the pragmatic factor to âforceâ the media to adopt the practical political logic for sake of increasing the images of the candidates. AbstrakPenelitian ini bertujuan mengetahui opini tokoh partai politik terhadap keberpihakan TV One dan Metro TV dalam Pilpres 2014, mengetahui besarnya peranan media dalam membentuk opini tokoh partai politik terhadap keberpihakan TV One dan Metro TV, dan tingkat keberpihakan TV O]]ne dan Metro TV sebagai TV nasional dalam pemilihan presiden 2014. Penelitian ini bersifat deskriptif kualitatif. Informan penelitian ini adalah 12 orang tokoh partai politik, 7 orang budayawan, pengamat politik dan Akdemisi. Penyampelan dilakukan secara purposif. Pengumpulan data dilakukan melalui wawancara dan observasi. Data dianalisis dengan menggunakan analisis model interaksi yang dikembangkan oleh Milles dan Huberman, data yang telah didapat kemudian diolah melalui 3 jalur analisis data kualitatif yaitu : Reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukan bahwa opini Tokoh Partai Politik terhadap keberpihakan TV One dan Metro TV pada Pilpres 2014cenderung berpihak kepada pasangan tertentu. Keberpihakan TV One kepada pasangan Prabowo-hatta dan Metro ke pasangan Jokowi- JK.. Demikianjuga peranan televisi dalam membentuk opini tokoh partai politik terhadap keberpihakan TV One dan Metro TV di Sulsel pada pilpres 2014 sangat besar. Hal ini dirasakan oleh seluruh informan baik yang tergabung dalam Koalisi Merah Putih maupun Koalisi Indonesia Hebat dengan tingkat keberpihakan TV One dan Metro TV pada pilpres 2014 sangat tinggi dirasakan oleh para tokoh partai politik di sulsel.Hal tersebut dimungkingkan karena faktor pragmatisme kepemilikan untuk âmemaksaâ media mengadopsi logika politik praktis yang untuk peningkatan citra kandidat.Â